Stratigraphy and Paleoecology of Quaternary Sediments Along Pasley River, Boothia Peninsula, Central Canadian Arctic - Dyke, Arthur; Matthews, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1987)
ABSTRACTQuaternary sediments exposed along Pasley River consist of a lower marine deltaic sand overlain in succession by complexly interbedded tills and glaciomarine sediments (the lower glacigenic assemblage), by a mid-section fluvial gravel, by an upper marine deltaic sand, and by glaciomarine sediment and till (the upper glacigenic assemblage). The midsection fluvial gravels contain plant and insect fossils indicating a climate as warm as and perhaps warmer than present. The top of the gravel is more than 55 000 years old ; the unit is probably of Sangamonian age (>75 000 ka) and separates Wisconsinan from lllinoian glacial deposits. The deltaic sands that underlie both glacigenic assemblages indicate substantial crustal depression during glacial buildup episodes prior to arrival of ice at the site. This implies that the process of buildup was slow and involved glacier expansion into major marine basins. Glaciomarine beds of the lower glacigenic assemblage locally contain abundant detrital terrestrial organic material as well as marine molluscs. The terrestrial organic detritus, an unusual constituent of glaciomarine sediment, is thought to have been released into the sea from glacier ice. These terrestrial fossil asemblages exhibit compositional differences which vary with the sediment faciès and probably reflect taphonomic factors such as differential buoyancy of the fossils. The upper marine deltaic sands contain some "old " rebedded plant detritus and amber indicating a nearby source of Tertiary sediment, possibly equivalent in age to the Beaufort Formation. Other rebedded fossils from the upper deltaic unit may be the same age as the mid-section fluvial gravels.